1988
DOI: 10.1073/pnas.85.19.7418
|View full text |Cite
|
Sign up to set email alerts
|

Extinction dynamics of age-structured populations in a fluctuating environment.

Abstract: We model density-independent growth of an age-(or stage-) structured population, assuming that mortality and reproductive rates fluctuate as stationary time series. Analytical formulas are derived for the distribution of time to extinction and the cumulative probability of extinction before a certain time, which are determined by the initial age distribution, and by the infinitesimal mean and variance, # and a2, of a diffusion approximation for the logarithm of total population size. These parameters can be es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
216
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(227 citation statements)
references
References 16 publications
6
216
0
1
Order By: Relevance
“…Notably, the observed distribution of persistence times closely followed that predicted by stochastic population growth theory in which extinction results from fluctuations in population size caused by environmental and/or demographic stochasticity (Lande & Orzack 1988;Dennis et al 1991;Engen et al 2005; both the inverse Gaussian and the demographic distributions fitted the data well).…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Notably, the observed distribution of persistence times closely followed that predicted by stochastic population growth theory in which extinction results from fluctuations in population size caused by environmental and/or demographic stochasticity (Lande & Orzack 1988;Dennis et al 1991;Engen et al 2005; both the inverse Gaussian and the demographic distributions fitted the data well).…”
Section: Discussionmentioning
confidence: 51%
“…For small populations, such as the introductions considered here, fluctuations in population size due to demographic and environmental stochasticity are likely to be the major cause of extinction (Richter-Dyn & Goel 1972). For populations unaffected by density dependence and subject only to fluctuations caused by environmental stochasticity, stochastic population growth theory predicts that the distribution of persistence times will approach an inverse Gaussian distribution with parameters specifying the initial population size or viability, the long-term population growth rate and the variance due to environmental stochasticity (Lande & Orzack 1988;Dennis et al 1991). The inverse Gaussian distribution is highly skewed with a long right tail, so that the theory predicts that populations will either go extinct quickly or persist for a long time (Claessen et al 2005).…”
Section: (A) Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total reproductive value equals the total population size N L if the population is exactly at its stable age distribution, and Engen et al (2007) showed that ln N L undergoes stationary fluctuations around ln V L with a return time to equilibrium of about one generation. That the process ln V L has approximately white noise explains the success of the diffusion approximation for ln V L (and ln N L ), identified simply as the Wiener process with infinitesimal mean and variancer L and s 2 L (Lande and Orzack 1988).…”
Section: Stochastic Demography and Reproductive Valuementioning
confidence: 99%
“…Because a diffusion process is subject to white noise with no temporal autocorrelation, the approximation is most accurate if the noise in the underlying biological process is approximately uncorrelated among years. Despite temporal autocorrelation in total population size produced by age-structure fluctuations, the stochastic demography of age-structured populations over timescales of a generation or more can nevertheless be accurately approximated by a diffusion process (Tuljapurkar 1982;Lande and Orzack 1988;Engen et al 2005aEngen et al , 2007. The success of the diffusion approximation for total population size occurs because the noise in the total reproductive value is nearly white, with no temporal autocorrelation to first order, and the log of total population size fluctuates around the log of reproductive value with a return time to equilibrium on the order of a few generations (Engen et al 2007).…”
mentioning
confidence: 99%